2008
DOI: 10.1108/02632770810840309
|View full text |Cite
|
Sign up to set email alerts
|

Perceived conditions of workers in different organizational settings

Abstract: Purpose -Research into office design and its effect on employee satisfaction and performance has attracted considerable contemporary research interest. However, most studies have tended to concentrate on the impact of the built environment on human performance, ignoring the actual needs of employees working in different organizational settings. This paper hence aims to investigate the nature and extent of occupant satisfaction with the built environment in different organizational settings in Australia for a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The current study adopts a survey technique and the data were collected through the use of a questionnaire. A questionnaire is a research instrument suitable for use in a survey setting like this, as it has already been used as a data collection tool in many similar studies (Batenburg and Voordt van der, 2008;Langston et al, 2008;De Been and Beijer, 2014). It quantifies formal aspects of unidirectional communication with the participants and offers an objective means of collecting information about people's knowledge, beliefs, attitudes and behavior, and is one of the most common forms of research.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study adopts a survey technique and the data were collected through the use of a questionnaire. A questionnaire is a research instrument suitable for use in a survey setting like this, as it has already been used as a data collection tool in many similar studies (Batenburg and Voordt van der, 2008;Langston et al, 2008;De Been and Beijer, 2014). It quantifies formal aspects of unidirectional communication with the participants and offers an objective means of collecting information about people's knowledge, beliefs, attitudes and behavior, and is one of the most common forms of research.…”
Section: Methodsmentioning
confidence: 99%
“…From the relevant literature (Davis et al, 2011;Kahler Slater, 2010;Myerson, 2009;Hameed and Amjad, 2009;Langston et al, 2008;Leaman and Bordass, 2005;Haynes, 2007b;Roelofsen, 2002), it seems that aspects of the contemporary workplace which can influence staff attitudes toward synergy and productivity are formed by a number of attributes, mainly: JFM 13,4…”
Section: The Concept Of the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…Low noise emission is acceptable and may even be useful to dampen the general noise level in open planned offices; however, when noise levels are intrusive a suitable contaminant or hearing protection partition can be used to drown out noise from office equipment (Joshi, 2008;Passarelli, 2009;Rostron, 2008). Research by Langston, Song and Purdey (2008) and All Business Consulting (2010) found that office noise is a potential obstacle to job satisfaction as it contributes to dissatisfaction within the physical environment and may filter through to the job. Significant correlates were also noted between noise and disruption in concentration (Banbury & Berry, 2005) and noise and stress (Evans & Johnson, 2000;Leather, Beale & Sullivan, 2003;Wallenius, 2004).…”
Section: Noise and Aestheticsmentioning
confidence: 99%
“…If the unhealthy environment persists then staff is often compelled to leave work seeking attractive employment elsewhere thereby contributing to increased staff turnover. Aside from the symptoms presented by physical and chemical components Fernberg, 1989;Heslop, 2003;Langston et al (2008); Muzi et al, 1997;Rooley, 1997), there is evidence that job stress and dissatisfaction can also exacerbate SBS if management fails to take cognizance of this in the workplace (Holman, 2003;Rostron, 2008; All Business Consulting, 2010).…”
Section: Health and Performancementioning
confidence: 99%